Risk factors, treatment, and outcome in dogs and cats with subdural hematoma and hemispheric collapse after ventriculoperitoneal shunting of congenital internal hydrocephalus - Daniela Farke; Anna K. Siwicka; Agnieszka Olszewska; Adriana Czerwik; Kathrin Büttner; Martin J. Schmidt (Journal of Veterinary Internal Medicine, 2023)
Abstract Background Overshunting and hemispheric collapse are well‐known complications after ventriculoperitoneal shunt (VPS) implantation. Risk factors that predispose to overshunting, treatment options, and prognosis after therapeutic intervention have not been described. Hypothesis/Objectives To identify preoperative risk factors for overshunting, the effect of surgical decompression, and their outcomes. Animals Seventy‐five dogs and 7 cats. Methods Retrospective case cohort study. Age, breed, sex, body weight, number of dilated ventricles, ventricle brain ratio, intraventricular pressure, and implanted pressure valve systems were evaluated as possible risk factors. Results Overshunting had a prevalence of 18% (Cl 95% 9.9‐26.66). An increase of 0.05 in VBR increased the risk of overshunting by OR 2.23 (Cl 95% 1.4‐3.5; P = .001). Biventricular hydrocephalus had the highest risk for overshunting compared to a tri‐ (OR 2.48 with Cl 95% 0.5‐11.1) or tetraventricular hydrocephalus (OR 11.6 with Cl 95% 1.7‐81.1; P = .05). There was no influence regarding the use of gravitational vs differential pressure valves (P > .78). Overshunting resulted in hemispheric collapse, subdural hemorrhage, and peracute deterioration of neurological status in 15 animals. Subdural hematoma was removed in 8 dogs and 2 cats with prompt postoperative improvement of clinical signs. Conclusions and Clinical Importance Biventricular hydrocephalus and increased VBR indicate a higher risk for overshunting. The use of differential valves with gravitational units has no influence on occurrence of overshunting related complications and outcomes. Decompressive surgery provides a favorable treatment option for hemispheric collapse and has a good outcome.